2022
DOI: 10.3390/en15061989
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Cr(VI) Remediation and Energy Production Using Microbial Fuel Cell from a Subsurface Environment: A Review

Abstract: Applying microbial fuel cell (MFC) technology for eco-remediation of Cr(VI) pollution from a subsurface environment has great scientific value and practical significance due to its promising advantages of pollutant remediation and renewable energy generation. The aim of the current review is to summarize the migration characteristics of Cr(VI) in a subsurface soil/water environment and investigate the factors affecting the MFC performance for synchronous Cr(VI) remediation and power generation, and sequentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 112 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…Nitrosomonas were the nitrogen transformation functional bacteria in the microbial fuel cell system [36]. Thiomona, Burkholderia, and Geobacter were EAB [37][38][39]. These findings indicated that bacteria associated with electrogenesis were the domain genera in MFCs.…”
Section: Microbial Community Of Anode Sludge In the Anaerobic Respira...mentioning
confidence: 83%
“…Nitrosomonas were the nitrogen transformation functional bacteria in the microbial fuel cell system [36]. Thiomona, Burkholderia, and Geobacter were EAB [37][38][39]. These findings indicated that bacteria associated with electrogenesis were the domain genera in MFCs.…”
Section: Microbial Community Of Anode Sludge In the Anaerobic Respira...mentioning
confidence: 83%
“…Hence, there is an urgent need to develop a sustainable method with low energy consumption and high removal efficiency for the treatment of heavy metal wastewater. Microbial fuel cells (MFCs), which can oxidize organic matter and reduce electron acceptors (usually O 2 ) have attracted increasing attention in removing organic matter and heavy metals from wastewater in recent years [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Cr(VI) recommended maximal permissible limit (MPL) in the surface water is regulated to 2 mg/L and to 0.1 mg/L in drinking water [9][10][11][12][13]. Naturally occurring Cr(VI) is found in ground and surface waters at values above 50 μg/L [6,14]. To meet these environmental standards/regulations, effluents and metal-polluted water must be treated prior to discharge into freshwater.…”
Section: ■ Introductionmentioning
confidence: 99%